A New C-Type Lectin Homolog SpCTL6 Exerting Immunoprotective Effect and Regulatory Role in Mud Crab Scylla paramamosain - Qiu, Wanlei; Chen, Fangyi; Chen, Roushi; Li, Shuang; Zhu, Xuewu; Xiong, Ming; Wang, Ke-Jian (Frontiers in Immunology, 2021)
C-type lectin (CTL), a well-known immune-related molecule, has received more and more attention due to its diverse functions, especially its important role in development and host defense of vertebrate and invertebrate. Since the research on crab CTLs is still lack, we screened a new CTL homolog, named SpCTL6 from mud crab Scylla paramamosain. The full-length cDNA sequence of SpCTL6 was 738 bp with a 486 bp of ORF, and the deduced amino acids were 161 aa. SpCTL6 was predicted to have a 17 aa signal peptide and its mature peptide was 144 aa (MW 16.7 kDa) with pI value of 5.22. It had typical CTL structural characteristics, such as a single C-type lectin-like domain, 4 conserved cysteines, similar tertiary structure to that of vertebrate CTLs and a mutated Ca2+ binding motif Gln-Pro-Thr (QPT), clustering into the same branch as the crustacean CTLs. SpCTL6 was highly expressed in the entire zoeal larval stages and widely distributed in adult crab tissues with the highest transcription level in testis. During the molting process of juvenile crabs, the expression level of SpCTL6 was remarkably increased after molting. SpCTL6 could be significantly upregulated in two larval stages (Z1 and megalopa) and adult crab testis under immune challenges. Recombinant SpCTL6 (rSpCTL6) was successfully obtained from eukaryotic expression system. rSpCTL6 exhibited binding activity with PAMPs (LPS, lipoteichoic acid, peptidoglycan, and glucan) and had a broad spectrum bacterial agglutination activity in a Ca2+-dependent manner. In addition, rSpCTL6 could enhance the encapsulation activity of hemocytes and has no cytotoxic effect on hemocytes. Although rSpCTL6 had no bactericidal activity on Vibrio alginolyticus, rSpCTL6 treatment could significantly reduce the bacterial endotoxin level in vitro and greatly improved the survival of S. paramamosain under V. alginolyticus infection in vivo. The immunoprotective effect of rSpCTL6 might be due to the regulatory role of rSpCTL6 in immune-related genes and immunological parameters. Our study provides new information for understanding the immune defense of mud crabs and would facilitate the development of effective strategies for mud crab aquaculture disease control.